Phase Difference between Horizontally and Vertically Polarized Microwave Signals During Sand Storms. (مجلة البيان العلمية, 2023)
This paper presents Some of the electrical and mechanical properties of sand and dust particles (SDP) are discussed. An expression for optical visibility during storms is given in terms of the relative volume occupied by dust. Expressions for attenuation and phase shift constants for a medium with precipitating dust particles are derived in terms of visibility and wavelength for both vertical and horizontal polarizations. Estimate phase difference between horizontal and vertical polarization which are needed  to estimate the attenuation and cross polarization of circularly polarized waves . Computations show that linearly polarized waves suffer but little effect. Circularly polarized waves on the other band are significantly cross polarized. In extremely severe dust conditions at frequencies around 8-12 GHz, phase difference between horizontal and vertical polarizations increases rapidly with decreasing visibility.
Keywords: vertical polarization; horizontal polarization; Cross polarization; Phase shift; Circular Polarization